Discovering Statistics Using IBM SPSS Statistics - Field Andy (Sage Publications, 2015)
This textbook provides students of statistical methods with everything they need to understand and use and report statistics - at every level. Preface, Acknowledgements, Why is My Evil Lecturer Forcing me to Learn Statistics?, Everything You Never Wanted to Know about Statistics, The IBM SPSS Statistics Environment, Exploring Data with Graphs, The Beast of Bias, Non-Parametric Models, Correlation, Regression, Comparing Two Means, Moderation and Mediation and More Regression, Comparing Several Means: ANOVA (GLM 1), Analysis of Covariance and ANOVA (GLM 2), Factorial ANOVA (GLM 3), Repeated - Measures Designs (GLM 4), Mixed Design ANOVA (GLM 5), Multivariate Analysis of Variance (MANOVA), Exploratory Factor Analysis, Categorical Data, Logistic Regression, Multilevel Linear Models, Epilogue: Life After Discovering Statistics, Glossary, Appendix, References, Index.